Highly Efficient Copper-Indium-Selenide Quantum Dot Solar Cells: Suppression of Carrier Recombination by Controlled ZnS Overlayers - Kim, Jae-Yup; Yang, Jiwoong; Yu, Jung Ho; Baek, Woonhyuk; Lee, Chul-Ho; Son, Hae Jung; Hyeon, Taeghwan; Ko, Min Jae (AMER CHEMICAL SOC, 2015)
Copper-indium-selenide (CISe) quantum dots (QDs) are a promising alternative to the toxic cadmium- and lead-chalcogenide QDs generally used in photovoltaics due to their low toxicity, narrow band gap, and high absorption coefficient. Here, we demonstrate that the photovoltaic performance of CISe QD-sensitized solar cells (QDSCs) can be greatly enhanced simply by optimizing the thickness of ZnS overlayers on the QD-sensitized TiO2 electrodes. By roughly doubling the thickness of the overlayers compared to the conventional one, conversion efficiency is enhanced by about 40%. Impedance studies reveal that the thick ZnS overlayers do not affect the energetic characteristics of the photoanode, yet enhance the kinetic characteristics, leading to more efficient photovoltaic performance. In particular, both interfacial electron recombination with the electrolyte and nonradiative recombination associated with QDs are significantly reduced. As a result, our best cell yields a conversion efficiency of 8.10% under standard solar illumination, a record high for heavy metal-free QD solar cells to date.
Keywords: COLLOIDAL NANOCRYSTALS; SHAPE CONTROL; CDSE; PROSPECTS; CUINSE2; SIZE; MULTIPLICATION; NANOPARTICLES; ELECTROLYTE; ENERGY